The Effect of Zinc Supplementation in Adult Patients with Acute Diarrhea - Deskian Kostermans; Marcellus Simadibrata; Irsan Hasan (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2014)
Background: Acute diarrhea is a common problem in developing country such as Indonesia with quite high morbidity andmortality rate. It was revealed that the level of zinc deficiency in adult acute diarrhea patients in several hospitals in Jakarta was 69.3%. Although zinc has been proven to be beneficial in the treatment of acute diarrhea in pediatric patients, the effect of zinc supplementation is not fully understood. The objective of this study was to discover the effectiveness of zinc supplementation as an adjuvant therapy in acute diarrhea for adult patients.Method: A double blind randomized controlled trial was done to discover the effect of zinc supplementation to the duration, signs and symptoms on acute diarrhea in hospitalized adults patients in Pertamina Central Hospital, Jakarta from January to December 2013. The data was analyzed using Chi-square test to compare the duration of diarrhea and general linear model (GLM) to assess changes of the symptoms accompanying diarrhea.Results: Data analysis from 84 patients, 30 males (19 zinc, 11 placebo) and 54 females (23 zinc, 31 placebo) with p = 0.111 showed that zinc supplementation significantly reduced the duration of acute diarrhea (p = 0.027) and nausea (p = 0.032). In addition there is a tendency of improvement in several acute diarrhea associated symptoms.Conclusion: Zinc supplementation significantly reduces the duration of diarrhea, nausea, as well as improving some symptoms accompanying acute diarrhea. Keywords: zinc supplementation, acute diarrhea, adult patient